The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.3892/ol_00000012
|View full text |Cite
|
Sign up to set email alerts
|

In vivo anti-tumor activity of photodynamic therapy with intravenous administration of acridine orange, followed by illumination with high-power flash wave light in a mouse osteosarcoma model

Abstract: Abstract. In a recent study, we demonstrated that a high-power flash wave light (FWL) from a xenon lamp exerted a stronger cytocidal effect against a mouse osteosarcoma cell line than continuous wave light (CWL) in photodynamic therapy with acridine orange (AO-PDT). Based on our in vitro results, we investigated the in vivo anti-tumor activity of AO-PDT using flash wave light from a xenon lamp in a mouse osteosarcoma model. Mouse osteosarcoma cells (LM8) were injected into the subcutaneous tissue of the back o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Acridine orange and other nuclear contrast agents such as acriflavine and proflavine, have been used as in vivo nuclear contrast agents for microscopy. [40][41][42][43][44] The use of nuclear contrast agents in vivo for neuropathologic assessment may be of importance because nuclear assessment is critical for the diagnosis of many neurologic tumors. Acridine orange has also been recently demonstrated as a potential agent for neuro-oncologic photodynamic therapy.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Acridine orange and other nuclear contrast agents such as acriflavine and proflavine, have been used as in vivo nuclear contrast agents for microscopy. [40][41][42][43][44] The use of nuclear contrast agents in vivo for neuropathologic assessment may be of importance because nuclear assessment is critical for the diagnosis of many neurologic tumors. Acridine orange has also been recently demonstrated as a potential agent for neuro-oncologic photodynamic therapy.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…When exposed to low doses of radiograph radiation, AO also increases the production of reactive radicals. 4 Kusuzaki et al 1 and Satonaka et al 3 , 7 developed photodynamic and radiodynamic therapies with AO (AO-PDT and AO-RDT) using in vitro and in vivo studies. In addition, other studies observed excellent clinical outcomes in patients with bone and soft-tissue sarcomas who received AO-PDT and AO-RDT.…”
Section: Introductionmentioning
confidence: 99%